2023
DOI: 10.2147/ijwh.s404845
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Toward Cervical Cancer Screening Among Female University Students in Ishaka Western Uganda

Abstract: Purpose Cervical cancer (CC) is the leading cause of cancer-related death among women living in third-world countries. CC is preventable, with the possibility of complete treatment if detected early. The objective of the study was to assess the level of knowledge, attitude, and practice on CC screening (CCS) among female university students (FUS) in Ishaka, western Uganda. Methods The study was a descriptive cross-sectional study among FUS (n = 407) in western Uganda co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…This percentage is lower than those found in similar studies conducted in other countries in Africa, namely a study held among students at the University of Buea in Cameroon by Halle-Ekane et al [ 5 ]. As little as 32.7% of the participants in this study had a positive attitude toward CC in Cabo Verde, which is in line with the results reported by Usman et al [ 33 ] (34,2%) in Uganda, and lower than those described by Getaneh et al [ 26 ] (67.7%), University of Northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…This percentage is lower than those found in similar studies conducted in other countries in Africa, namely a study held among students at the University of Buea in Cameroon by Halle-Ekane et al [ 5 ]. As little as 32.7% of the participants in this study had a positive attitude toward CC in Cabo Verde, which is in line with the results reported by Usman et al [ 33 ] (34,2%) in Uganda, and lower than those described by Getaneh et al [ 26 ] (67.7%), University of Northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we believed that the higher percentage of educated people in the community influenced the decision of community dwellers to undergo the CXR screening as well. Our finding was supported by those studies assessing the impact of health knowledge, attitudes, and the health belief model on disease screening ( 10 , 26 , 27 , 32 , 33 ) Most of the current studies evaluated the impact of the HBM on the decision of people to undergo breast, cervical, lung, or colonic cancer screening ( 34 38 ). No studies discussing PTB screening in the community are available.…”
Section: Discussionsupporting
confidence: 81%
“…Then, self-efficacy and self-confidence for conducting the advised health practices will be formed in the program participants. It was suggested that the HBM alone or enhanced by self-efficacy, a high level of knowledge, or attitudes toward disease prevention were important motivators for high adoption and adherence to a health program ( 4 6 , 24 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher anxiety toward cancer has been reported to increase the rates of colon and breast cancer screening [ 25 , 26 ]. Nevertheless, the KAP toward screening for various cancers is generally poor, but the presence of symptoms generally appears as an incentive [ [14] , [15] , [16] ]. The presence of neurological symptoms, especially non-specific ones like headaches and seizures, can be worrisome since they cannot be directly linked to a specific disease before investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the KAP toward cancer in general was very variable among different populations [ [10] , [11] , [12] , [13] , [14] ], including cancer screening [ [14] , [15] , [16] ]. KAP studies were performed in patients with glioma [ 17 , 18 ] and healthcare providers [ 19 ], but no data are available regarding the KAP toward glioma of patients consulting for neurological symptoms in general.…”
Section: Introductionmentioning
confidence: 99%